ASSESSING THE BENEFITS AND VALUES IN IMPLEMENTING THE TRADITION OF ALMIGHTY EARTH FROM THE VIEW OF FUNCTIONALISM THEORY - Martin Rizaldi; Anin Lailatul Qodariyah (Universitas Galuh, 2021)
This article aims to understand the benefits of values in the implementation of the earth alms tradition from the point of view of functionalism theory. The method of preparing this article uses the heirloom study method, which uses reference sources from books and journals. In Indonesia, there are many kinds of traditions, one of which is the earth alms tradition, which is a tradition in the form of traditional celebrations aimed at the earth as a form of public gratitude for the salvation given by the Almighty Creator. In the earth alms tradition, there are various ritual activities that are carried out, and there are benefits and values that can be studied with functionalism theory such as faith values, worship values, social values, cultural values, and philosophical values.